Gender and cognitive factors influencing information seeking of graduate students at Kenyatta University Library - Johnson M. Masinde; Daniel M. Wambiri; Jing Chen (South African Journal of Information Management, 2020)
Background: Gender has been identified as a possible influencing factor in users’ information-seeking process. Previous studies have alluded to the fact that gender as a variable may be useful for a better understanding of the cognitive and social background of human information processing and may have important implications in the information-seeking process. Although a number of studies have investigated gender, amongst other variables, as having an effect on the information-seeking process of users, no attempt has been made to investigate the relationship between gender and cognitive factors on the information-seeking patterns of graduate students of Kenyatta University Library.